Trajectories of Discrimination Across Adolescence: Associations With Academic, Psychological, and Behavioral Outcomes. Issue 5 (September 2016) - Hughes, Diane; Del Toro, Juan; Harding, Jessica F.; Way, Niobe; Rarick, Jason R. D.
Abstract : The authors explored trajectories of perceived discrimination over a 6‐year period (five assessments in 6th–11th grade) in relation to academic, behavioral, and psychological adjustment in 8th and 11th grades. They distinguished discrimination from adults versus peers in addition to overt versus covert discrimination from peers. The sample included 226 African American, White, Dominican, Puerto Rican, and Chinese adolescents (ages 11–12 at Time 1) recruited in sixth grade from six public schools in New York City. All forms of discrimination increased during middle school and decreased during high school. The frequency with which adolescents reported different sources and types of discrimination varied across ethnicity/race, but not gender. Initial levels and rates of change in discrimination predicted academic, behavioral, and psychological adjustment in 8th and 11th grades, albeit in complex ways.